Mitochondrial Genome Study Identifies Association Between Primary Open-Angle Glaucoma and Variants in MT-CYB, MT-ND4 Genes and Haplogroups - Lo Faro, Valeria; Nolte, Ilja M.; Ten Brink, Jacoline B.; Snieder, Harold; Jansonius, Nomdo M.; Bergen, Arthur A.; Lifelines Cohort Study, (Frontiers in Genetics, 2021)
Background and purpose: Primary open-angle glaucoma (POAG) is an optic neuropathy characterized by death of retinal ganglion cells and atrophy of the optic nerve head. The susceptibility of the optic nerve to damage has been shown to be mediated by mitochondrial dysfunction. In this study, we aimed to determine a possible association between mitochondrial SNPs or haplogroups and POAG. Methods: Mitochondrial DNA single nucleotide polymorphisms (mtSNPs) were genotyped using the Illumina Infinium Global Screening Array-24 (GSA) 700K array set. Genetic analyses were performed in a POAG case-control study involving the cohorts, Groningen Longitudinal Glaucoma Study-Lifelines Cohort Study and Amsterdam Glaucoma Study, including 721 patients and 1951 controls in total. We excluded samples not passing quality control for nuclear genotypes and samples with low call rate for mitochondrial variation. The mitochondrial variants were analyzed both as SNPs and haplogroups. These were determined with the bioinformatics software HaploGrep, and logistic regression analysis was used for the association, as well as for SNPs. Results: Meta-analysis of the results from both cohorts revealed a significant association between POAG and the allele A of rs2853496 (odds ratio (OR)=0.64; p=0.006) within the MT-ND4 gene, and for the T allele of rs35788393 (OR=0.75; p=0.041) located in the MT-CYB gene. In the mitochondrial haplogroup analysis, the most significant p-value was reached by haplogroup K (p = 1.2x10-05), which increases the risk of POAG with an OR of 5.8 (95% CI 2.7-13.1). Conclusions: We identified an association between POAG and polymorphisms in the mitochondrial genes MT-ND4 (rs2853496) and MT-CYB (rs35788393), and with haplogroup K. The present study provides further evidence that mitochondrial genome variations are implicated in POAG. Further genetic and functional studies are required to substantiate the association between mitochondrial gene polymorphisms and POAG and to define the pathophysiological mechanisms of mitochondrial dysfunction in glaucoma.